Persepsi Penutur Asing Terhadap Bahan Ajar Bahasa Indonesia Berbasis Kearifan Lokal - Nur Afnia; Kembong Daeng; Hasriani Hasriani (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2025)
This research aims to describe the perceptions of foreign speakers towards Indonesian language teaching materials based on local wisdom. This research is qualitative research with a qualitative descriptive research design. The data source in this research is foreign speakers who are studying Indonesian at the Bolasugi Language School. Research data was obtained by asking several questions that had been provided by the researcher. Data analysis was carried out using data reduction, data presentation, and data verification. The results of the research and discussion can be concluded that foreign speakers have a positive perception of local wisdom-based teaching materials. They feel that these teaching materials not only help in learning Indonesian, but also introduce local culture in an interesting and relevant way and that local wisdom-based teaching materials are able to achieve learning goals, such as improving language understanding, enriching vocabulary, and growing foreign speakers' confidence in using Indonesian.